DAMPAK INOVASI DESAIN INTERIOR PERPUSTAKAAN RAMAH ANAK TERHADAP PERILAKU EDUKATIF PADA SISWA SEKOLAH DASAR DI KABUPATEN TEGAL - Rullis, Rullis; Muljani, Sutji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low reading interest among elementary students in Indonesia is often exacerbated by rigid, non-ergonomic, and visually unappealing library conditions. This study aims to analyze the impact of child-friendly library interior design innovations on the formation of educational behavior among students in Tegal Regency. Employing a qualitative approach with a case study design, the research was conducted in three elementary schools participating in the Child-Friendly Library program. Data were collected via participatory observation, structured interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that interior design transformations focusing on physical elements (vibrant colors, zoning, ergonomic furniture), environmental aspects, and inclusivity successfully created a more stimulating and comfortable library atmosphere. This spatial transformation significantly impacted students' educational behaviors, evidenced by increased independent visit initiatives (reading interest), longer reading focus duration (persistence), and collaborative social interactions during literacy activities. It is concluded that library interior design serves not merely as an aesthetic improvement, but as a vital pedagogical instrument in fostering a sustainable literacy culture in schools